Polyphenolic substrates and dyes degradation by yeasts from 25 de Mayo/King George Island (Antarctica) - Rovati, Jose Ignacio; Pajot, Hipólito Fernando; Ruberto, Lucas Adolfo Mauro; Mac Cormack, Walter Patricio; Castellanos de Figueroa, Lucia Ines (Yeast)
Antarctica offers a range of extreme climatic conditions, such as low temperatures, high solar radiation and low nutrient availability, and constitutes one of the harshest environments on Earth. Despite that, it has been successfully colonized by 'cold-loving' fungi, which play a key role in decomposition cycles in cold ecosystems. However, knowledge about the ecological role of yeasts in nutrient or organic matter recycling/mineralization remains highly fragmentary. The aim of this work was to study the yeast microbiota in samples collected on 25 de Mayo/King George Island regarding the scope of their ability to degrade polyphenolic substrates such as lignin and azo dyes. Sixty-one yeast isolates were obtained from 37 samples, including soil, rocks, wood and bones. Molecular analyses based on rDNA sequences revealed that 35 yeasts could be identified at the species level and could be classified in the genera Leucosporidiella, Rhodotorula, Cryptococcus, Bullera and Candida. Cryptococcus victoriae was by far the most ubiquitous species. In total, 33% of the yeast isolates examined showed significant activity for dye decolorization, 25% for laccase activity and 38% for ligninolytic activity. Eleven yeasts did not show positive activity in any of the assays performed and no isolates showed positive activity across all tested substrates. A high diversity of yeasts were isolated in this work, possibly including undescribed species and conspicuous Antarctic yeasts, most of them belonging to oligotrophic, slow-growing and metabolically diverse basidiomycetous genera. Fil: Rovati, Jose Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina Fil: Pajot, Hipólito Fernando. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina Fil: Ruberto, Lucas Adolfo Mauro. Universidad ...